Site-Specific Clinical Evaluation of the Luminex xTAG Gastrointestinal Pathogen Panel for Detection of Infectious Gastroenteritis in Fecal Specimens - Patel, Anami (American Society for Microbiology, 2014)
We evaluate the clinical performance of the Luminex xTAG gastrointestinal (GI) pathogen in vitro diagnostic (IVD) assay in a comparison between clinical and public health laboratories. The site reproducibility study showed 98.7% sensitivity with high positive and negative agreement values (96.2% and 99.8%, respectively), while assay performance against confirmatory methods resulted in 96.4% sensitivity with similar positive and negative agreement values (90.1% and 99.5%, respectively). High-throughput detection of multiple GI pathogens improved turnaround time, consolidated laboratory workflow, and simplified stool culture practices, thus reducing the overall cost and number of specimens processed.